Framing Social Reality : The Relevance of Relational Judgments - DILLARD, JAMES PRICE and SOLOMON, DENISE HAUNANI and SAMP, JENNIFER ANNE (Communication Research, 1996)
Relational communication researchers have asserted that dominance and affiliation are the fundamental features of social reality. The authors argue that when individuals interpret interaction, they focus on one dimension or the other, such that dominance and affiliation are differentially salient. On that premise, the authors hypothesized that the relative salience of dominance or affiliation would be a function of the goal-defined context. Further, some investigators have argued that the notion of involvement is also essential to the study of relational communication. Although the authors concur, they believe that involvement is a fundamentally different type of construct than dominance or affiliation. The authors hypothesized that involvement is relevant to both dominance and affiliation judgments; it functions as an intensifier variable. A study was conducted in which participants rated the relevance of a series of word pairs that operationalized dominance, affiliation, and involvement within 12 interaction scenarios. Although there was evidence that the biological sex of the judge moderated the magnitude of some effects, the results were uniformly supportive of the hypotheses.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwOTYwMjMwMDYwMDQ